Microbial degradation of the herbicide molinate by defined cultures and in the environment - Olga C. Nunes (2013)
Molinate is a thiocarbamate herbicide used worldwide in rice crop protection. As with other pesticides, molinate is a recognized environmental pollutant, detected in soils, irrigation water, or rivers and bio-accumulated by some wildlife forms. For this reason, and in spite of its low toxicity to humans, environmental protection measures, which include reduction of use and/or remediation processes, are recommended. Due to its physic-chemical properties, molinate can easily disperse and react in the environment, originating diverse transformation products, some with increased toxicity. In spite of being a xenobiotic compound, molinate can also suffer microbial transformation by bacteria or fungi, sometimes serving as nutrient and energy source. In an attempt to isolate microorganisms to be used in the bioremediation of molinatecontaminated sites, a mixed culture, dominated by the actinobacterium Gulosibacter molinativorax ON4T, was recovered from the runoff of a molinate-producing plant. Beyond a promising tool to decontaminate molinate-polluted sites, this culture also brought interesting insights into the biology of the degradation of this herbicide. In this review, an overview of the distribution and properties of molinate as environmental contaminant, the capability of microorganisms to transform this herbicide, and some reflections about possible bioremediation approaches are made. Â(c) Springer-Verlag Berlin Heidelberg 2013.